2019
DOI: 10.1002/ehf2.12471
|View full text |Cite
|
Sign up to set email alerts
|

Blood urea nitrogen variation upon admission and at discharge in patients with heart failure

Abstract: Aims Heart failure (HF) is one of the leading causes for hospitalization and mortality. After first admission with acute decompensated HF, some patients are in high risk for short‐term and long‐term mortality. These patients should be identified, closely followed up, and treated. It has been observed that blood urea nitrogen (BUN) on admission is a predictive marker for short‐term mortality. Recently, it has been shown that higher BUN levels on discharge are also a bad prognostic predictor. However, the progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
(34 reference statements)
2
22
0
Order By: Relevance
“…Blood urea nitrogen level at admission is defined as a predictor of worse outcome in heart failure 30 and AECOPD. 31 In parallel, we found higher ED revisit rates with higher urea levels.…”
Section: Discussionmentioning
confidence: 99%
“…Blood urea nitrogen level at admission is defined as a predictor of worse outcome in heart failure 30 and AECOPD. 31 In parallel, we found higher ED revisit rates with higher urea levels.…”
Section: Discussionmentioning
confidence: 99%
“…5 Cardiology Department, Rambam Health Care Campus, Haifa, Israel. 6 Internal Medicine Department H, Rambam Health Care Campus, Haifa, Israel. 7 Medicine Department D, Rambam Health Care Campus, Haifa, Israel.…”
Section: Openmentioning
confidence: 99%
“…A number of laboratory markers has been associated with increased risk of short term mortality, Blood Urea Nitrogen (BUN) and natriuretic peptides level both in admission and discharge were associated with increased risk for short term mortality [4][5][6][7] .…”
mentioning
confidence: 99%
“…To the best of our knowledge, no study in the literature has investigated the predictive value of higher urea for the mortality rates of patients who undergo PEG insertion. Nonetheless, some studies have indicated that urea levels can be used to predict shortterm mortality rates in cardiac diseases (19). Moreover, Sbeit et al indicated that creatinine and some other parameters could predict short-term mortality after PEG (20).…”
Section: Discussionmentioning
confidence: 99%